Psikososial pada Guru Penyintas Bencana Gempa Bumi di Cianjur Jawa Barat - Zakiah, Ernita; Erik; Putri, Fildzah Rudyah; Mayangsari, Anggi; Akbar, Zarina; Maulidia, Elisa Az-Zahra; Kartika, Vera (Jendela Akademika, 2024)
This community service aims to provide post-disaster psychological handling assistance to teachers at SDN Sukamaju 1, Benjot Village, Cugenang District, Cianjur Regency, West Java. The approach given is psychosocial. Psychosocial was given to 8 teachers. Psychosocial is given to teachers through lectures, games, and simulations. The results of community service show that teachers feel happy, know how to manage emotions and perform the first rescue in case of disaster. The impact of psychosocial provided helps teachers to have skills in managing emotions, knowledge of disasters, and enthusiasm in carrying out teaching and learning activities in the future.